Isolation, Screening, and Active Metabolites Identification of Anti-Vibrio Fungal Strains Derived From the Beibu Gulf Coral - Huang, Bingyao; Peng, Shuai; Liu, Shifang; Zhang, Yanting; Wei, Yuxiao; Xu, Xinya; Gao, Chenghai; Liu, Yonghong; Luo, Xiaowei (Frontiers in Microbiology, 2022)
The Beibu Gulf harbors abundant underexplored marine microbial resources which are rich in diversified secondary metabolites. The genera Vibrio is a well-known pathogenic bacterium of aquatic animals. In this study, 22 fungal strains were isolated and identified from the Beibu Gulf coral via the serial dilution method and internal transcribed spacer (ITS) sequence analysis, which were further divided into three branches by phylogenetic tree analysis. The crude extracts of them via small-scale fermentation were selected for the screening of inhibitory activity against Vibrio alginalyticus, V. coralliilyticus, V. harveyi, V. parahaemolyticus, V. owensii, and V. shilonii. The results showed that 8 fungal extracts displayed anti-Vibrio activity via the filter paper disk assay. Several of them showed strong inhibitory effects. Then, two tetramic acid alkaloids, equisetin (1) and 5'-epiequisetin (2), were identified from Fusarium equiseti BBG10 by bioassay-guided isolation, both of which inhibited the growth of Vibrio spp. with the MIC values of 86–132 μg/mL. The scanning electron microscope results showed that cell membranes of Vibrio became corrugated, distorted or ruptured after treatment with 1 and 2. Taken together, this study provided 8 fungal isolates with anti-Vibrio potentials, and two alkaloid-type antibiotics were found with anti-Vibrio effects from the bioactive strain F. equiseti BBG10. Our findings highlight the importance of exploring promising microbes from the Beibu Gulf for the identification of anti-Vibrio for future antibiotic development.